PENCATATAN KEUANGAN DIGITAL BERBASIS ANDROID PADA CV. YUDAWASTU KENCANA KABUPATEN SUKABUMI - Umami, Nida Auliana; Nurani, Rahma (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
According to the Creative Economy Agency, there are still many MSMEs that do not have good financial records so that they are not able to prepare financial reports. Indonesian business actors still record their business finances and stocks manually. In fact, digitizing the recording process in business is not only to make it easier, but also to improve the accuracy of inventory and financial reports which have an impact on long-term business credibility. The development of technology is utilized by Bank Indonesia (BI) in collaboration with the Indonesian Accountants Association (IAI) to help MSMEs by launching a financial transaction recording application that is in accordance with SAK EMKM called the Financial Information Recording Application Information System (SI APIK). This study aims to implement digital financial recording using the SI APIK application in MSMEs in accordance with applicable accounting standards. The research method that the author uses is qualitative which is an approach in conducting research that is oriented towards natural phenomena or symptoms with data collection techniques including: observation, interviews, and literature studies. The results of this study found that the application of financial records through the SI APIK application in MSMEs can determine the net profit obtained by these MSMEs and can make financial reports on businesses that are run in accordance with the financial accounting standards of micro, small and medium entities.